Value Input Application (E-Pak) Functional Position of Bandung City Health Department Based on Web Database - Syahrul Zein; Onoy Rohaeni; Farid Badruzzaman; Yusuf Fajar; Didi Suhaedi; Erwin Harahap (International Journal of Quantitative Research and Modeling, 2022)
Technology is present and becomes a part of human life. Each era has its own technological advantages. The history of technology begins millions of years ago. The first technology discovered by mankind was to create sharp stone chips which were used as stones. Then humans began to develop and found several technologies, one of which was computers and the internet. computers and the internet have a close relationship, especially in today's era where all activities cannot be separated from computers and the internet. One of these activities is in the office world. The Bandung City Health Office is a government agency that has a lot of data, especially in the section where the author is placed, namely the Division of Human Resources and Health or SDMK. The SDMK Division is tasked with receiving data on the credit score of a functional position from the assessment team to calculate whether a functional position is eligible for promotion or not. On that basis, the purpose of this paper is to create an application for inputting the credit score for a functional position based on a web database to make it easier for the assessment team, SDMK to view, recap and change credit scores as well as a functional position in viewing its credit score. The main finding is a web database-based application called E-PAK.